2003
DOI: 10.1354/vp.40-4-405
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Herpes simplex Infection in a Group of Common Marmosets (Callithrix jacchus)

Abstract: Abstract. An outbreak of classical herpetic infection causing vesicoulcerative stomatitis in a family group (eight animals) of Callithrix jacchus is described. In all eight infected animals, human herpesvirus 1 (HHV-1) was identified as the causative agent. This was confirmed by histologic, immunohistologic, and molecular biologic investigations, as well as by virus isolation. The clinical picture, the macroscopic appearance, and the histologic results indicated a herpes infection as the cause of mortality. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 10 publications
7
64
1
5
Order By: Relevance
“…Based on the epidemiology of the cases in this study, it was verified that Neotropical primates are highly susceptible to HHV-1 (Melendez et al 1969, Murphy et al 1972, Bruno et al 1997, Juan-Sallés et al 1997, Huemer et al 2002, Matz--Rensing et al 2003, Schrenzel et al 2003, Hatt et al 2004, Lefaux et al 2004, Gozalo et al 2008, Longa et al 2011. This virus causes an acute and fatal disease in marmosets, characterized by multiple skin vesicles and ulcers as well as severe necrotizing meningoencephalitis (Juan-Sallés et al 1997, Hatt et al 2004, Lefaux et al 2004, Longa et al 2011.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Based on the epidemiology of the cases in this study, it was verified that Neotropical primates are highly susceptible to HHV-1 (Melendez et al 1969, Murphy et al 1972, Bruno et al 1997, Juan-Sallés et al 1997, Huemer et al 2002, Matz--Rensing et al 2003, Schrenzel et al 2003, Hatt et al 2004, Lefaux et al 2004, Gozalo et al 2008, Longa et al 2011. This virus causes an acute and fatal disease in marmosets, characterized by multiple skin vesicles and ulcers as well as severe necrotizing meningoencephalitis (Juan-Sallés et al 1997, Hatt et al 2004, Lefaux et al 2004, Longa et al 2011.…”
Section: Discussionmentioning
confidence: 55%
“…Although many cases of HHV-1 in marmosets demonstrate little systemic involvement, (Juan-Sallés et al 1997, Matz-Rensing et al 2003, Hatt et al 2004, Lefaux et al 2004, this study verified widespread viral antigen throughout many organs using immunohistochemistry. In this study was observed that anti-HHV-1 immunostaining was more frequent in the brain (12/12) and mucosa of oral cavity and tongue (5/12).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations